MENINGKATKAN BUDAYA LITERASI MELALUI TAMAN BACA MASYARAKAT DESA RAJADANU KABUPATEN KUNINGAN - Nurhayati, Ita; Pratomi, Yogi; Aryanto, Aryanto; Fahri, Amar; Alfin, Muhamad; Fahrezi, Rifki; Syifa, Syifa; Maulana, Aldy; Fuadi, Wafa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
The aim of this activity is to stimulate interest in literacy among children, especially in Rajadanu Village, and the general public, with a focus on improving literacy skills. In implementing this reading garden program, we apply research-bSased methods with a PAR (Participatory Action Research) approach. When providing books, we also work with book donors. Apart from that, the village also provides space for the TBM. Based on observations, it indicates that children's reading awareness in Rajadanu Village is still lacking. Providing reading books is an important factor in stimulating interest in reading, and good facilities can promote people's interest in reading, especially local children. The conclusion of this service is an effort to stimulate or improve children's literacy understanding through reading gardens.